Viability of rearing Telenomus sp. (Hymenoptera, Scelioniodae), an egg parasitoid of Helicoverpa armigera (Lepidoptera, Noctuidae), under laboratory conditions - Duarte, S.=700 1 Goncalves, C.I.
(En, Es)